THE EFFECT OF JOB SATISFACTION AND JOB DISCIPLINE TOWARD SALESPERSON EMPLOYEE PERFORMANCE AT TOYOTA HADJI KALLA SUBDIVISION URIP SUMOHARJO MAKASSAR - Nurdin Brasit; Jusni; Nur Fadillah (The Scientia Law and Economics Review, 2023)
This study aims to determine the effect job satisfaction and job discipline toward salesperson employee performance At Toyota Hadji Kalla Subdivision Urip Sumoharjo Makassar. This research is a quantitative research with a survey method. The population of this study were all employees who work as salespeople at the Toyota Hadji Kalla Office, Urip Sumoharjo Makassar Branch, as many as 42 people. The research sample used the census method as many as 42 respondents. The data collection technique is a questionnaire using a Likert scale. The data analysis technique used the computerized SPSS program. The results of this study indicate that there is an effect of satisfaction and job discipline toward salesperson employee performance at Toyota Hadji Kalla Subdivision Urip Sumoharjo Makassar.